Towards Building Circularity in Queensland: Policy Gaps in the Built Environment - Thaher, Yousef A. Y.; Schork, Tim; Pushpamali, NNC; Cowled, Craig; Crowther, Philip (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This study evaluates Queensland’s policies supporting circular economy practices in the building and construction industry. Through systematic review, it reveals that while current initiatives have improved construction waste recovery rates, policies focus primarily on recycling rather than higher-order circular practices like deconstruction and material reuse. The research identifies opportunities for policy reform and incentives to advance Queensland’s transition to a circular economy in the built environment.